Distribution and Abundance of Big-Leaf Mahogany (Swietenia macrophylla) on the Yucatan Peninsula, Mexico. (April 2018) - Navarro-Martínez, Angélica; Ellis, Edward A.; Hernández-Gómez, Irving; Romero-Montero, José Arturo; Sánchez-Sánchez, Odilón
Big-leaf mahogany ( Swietenia macrophylla King) is an economically important timber species in the Neotropics. For over three centuries, it has been selectively extracted from tropical forests, threatening its populations. We investigate the actual and potential distribution of big-leaf mahogany and assess its abundance on the Yucatan Peninsula based on the National Forest and Soils Inventory database. Furthermore, we evaluate environmental factors associated with its distribution, abundance, and tree size. The actual and potential distribution models show the presence of mahogany in a wide geographic area covering the southern and eastern portions of the Yucatan Peninsula. Abundance of mahogany in the landscape varies and in general is low. The spatial potential distribution model was best explained by the environmental variables of vegetation cover (medium- and high-stature semievergreen tropical forest) and elevation (upland areas). Results also indicate that mahogany remains relatively abundant and contain larger size classes in localities where the species has been harvested and managed for decades under community forest management. Furthermore, statistical analyses show greater tree density of mahogany mostly associated with low-stature semievergreen tropical forest having deep soils (gleysols and vertisols), while larger tree size (diameter at breast height) was associated with medium-stature semievergreen tropical forests in upland areas with moderately deep or shallow soils (mostly rendzinas or leptosols). Despite deforestation, land-use change and forestry activities on the Yucatan Peninsula, particularly in the past 20 years, the distribution and abundance of mahogany do not appear to be as drastically reduced as described in other neotropical regions.